THE LEGAL PROTECTION OF CLICKWRAP AGREEMENT IN THE ELECTRONIC CONTRACT OF ELECTRONIC COMMERCE TRANSACTIONS - Tuturoong, Veronica; Herry, Musleh (Fakultas Syariah, 2021)
E-contract is a new technology in online trading. It is a double-edged sword. Besides having advantages such as simplifying and speeding up transactions, it has shortcomings e.g. no legality regarding e-contract and substantive and procedural problems. One of them is in the application of clickwrap agreements, a standard agreement in e-commerce transactions. Buyers must agree with the requirements by clicking the â€œI agreeâ€ button. The research examines the legal protection and privacy policy for the users of smart contract clickwrap agreements in e-commerce transactions in Indonesia. This is normative research with a statute approach. This study teaches the readers to understand the shortcomings and to be more cautious about e-commerce transactions. The results reveal that privacy policy on the use of smart contract clickwrap agreement is based on the EIT Law meanwhile the international law aspect is UNCITRAL Model Law. It shows that e-contract basic guideline has law absence. Besides investigating the regulations, the researchers trace the principles of contract law which is applicable to realize justice and certainty of parties. To conclude, legal reformation is needed in managing the validity of the smart contract clickwrap agreement so there will be legal certainty in e-commerce transactions in Indonesia.E-contract merupakan teknologi baru yang diterapkan dalam perdagangan online. E-contract merupakan pedang bermata dua. Di samping memiliki banyak keuntungan seperti mempermudah dan mempercepat transaksi, namun ia juga memiliki kekurangan, seperti tidak adanya legalitas mengenai e-contract dan permasalahan yang bersifat substantif dan prosedural. Salah satunya ialah penerapan clickwrap agreement, bentukÂ perjanjian baku dalam transaksi e-commerce. Pembeli harus menyetujui persyaratan dengan mengklik tombol â€œI agreeâ€. Penelitian ini mengkaji perlindungan hukum dan kebijakan privasi bagi pengguna smart contract clickwrap agreement pada transaksi e-commerce di Indonesia. Metode yang digunakan ialah penelitian normatif dengan pendekatan perundang-undangan. Penelitian ini mengajarkan pembaca untuk lebih memahami kekurangan dan waspada dalam melakukan transaksi e-commerce. Hasil penelitian menunjukkan bahwa kebijakan privasi pada penggunaan smart contract clickwrap agreement berdasarkan UU ITE dan aspek hukum internasional yaitu UNCITRAL Model Law sebagai pedoman dasar e-contract masih memiliki kekosongan hukum. Selain menelusuri peraturang perundangâ€“undangan peneliti juga menelusuri asasâ€“asas hukum kontrak yang dapat diterapkan untuk mewujudkan keadilan dan kepastian para pihak. Dapat disimpulkan bahwa diperlukan pembaharuan hukum dalam pengaturan keabsahan smart contract clickwrap agreement agar terbentuk kepastian hukum dalam transaksi elektronik di Indonesia.